Development of ownership of patient care during clerkship - Leblanc, Andréanne; Snell, Linda; Sun, Ning-Zi (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Background: Ownership of patient care is a concept that embodies a number of professionalism attributes and involves a feeling of strong commitment and responsibility towards patient care. Little is known about how the embodiment of this concept develops in the earliest stages of clinical training. The goal of this qualitative study is to explore the development of ownership of patient care in clerkship.Methods: Using qualitative descriptive methodology, we conducted twelve one-on-one in-depth semi-structured interviews with final-year medical students at one university. Each participant was asked to describe their understanding and beliefs with regards to ownership of patient care and discuss how they acquired these mental models during clerkship, with emphasis on enabling factors. Data were inductively analyzed using qualitative descriptive methodology and with professional identity formation as the sensitizing theoretical framework.Results: Ownership of patient care develops in students through a process of professional socialization that includes enabling factors such as role modelling, student self-assessment, learning environment, healthcare and curriculum structures, attitudes of and treatment by others, and growing competence. The resulting ownership of patient care is manifested as understanding patients’ needs and values, engaging patients in their care, and maintaining a strong sense of accountability for patients’ outcome.Conclusion: An understanding of how ownership of patient care develops in early medical training and the associated enabling factors can inform strategies aimed at optimizing this process, such as designing curricula with more opportunities for longitudinal patient contact and fostering a supportive learning environment with positive role modelling, clear attribution of responsibilities, and purposefully granted autonomy.